Keterampilan Berpikir Kritis Siswa SMP dalam Menyelesaikan Masalah Matematika Kontekstual Ditinjau dari Kemampuan Matematika - Indan Afifah Rahmawati; Pradnyo Wijayanti (Program Studi S1 Matematika UNESA, 2023)
One of the important skills to be mastered by students is critical thinking skills. One way to bring up students' critical thinking skills is by confronting them with a problem. The context of the problem that is closest and can be recognized well by students is the context of daily life or is called contextual problem. This research is a qualitative descriptive study. The subjects of this study were three students of 8th grade at SMP Negeri 1 Kedunggalar with each student having high, medium and low mathematical abilities. The method of collecting data in this study is through tests of mathematical abilities, tasks of solving contextual mathematical problems, and interviews. The results showed that junior high school students had high, medium, and low math skills in clarification skills, namely students wrote down the information they knew about questions such as the size of tiles, the size of the library floor, and discounts. Students formulate the main problem, namely finding the cheapest price from a choice of two ceramics, with the concept used, namely the area of a square and a rectangle. In the assessment skills, students assess the information previously mentioned as sufficient to solve the problem and mention the relevance of the information to the completion step, namely the size of the tile area and the area of the library to determine the number of tiles needed. In inference skills, students with high and moderate mathematical abilities show a relationship of ideas related to the steps used, namely finding the number of ceramics, the total price, and the price after the discount. In strategy skills, students evaluate the steps used by reviewing the results of the completion that has been done. Meanwhile students with low mathematical abilities did not describe the relationship from the information known to the problem and could not evaluate the results of the solution.